Digitalisasi Preparat Mikroskopis Plasmodium falciparum dan Plasmodium vivax Sebagai Media Pembelajaran Protozoologi - Anindita, Reza; Nathalia, Dede Dwi; Rahmadi, Chandra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
One of the competencies of health students in the health protozoology course is being able to identify the microscopic morphology of Plasmodium sp. However, the identification of Plasmodium sp. is still widely done using conventional ATLAS. Therefore, innovation is needed using digital ATLAS. The purpose of this study was to digitize microscopic images of Plasmodium vivax and falciparum as a learning medium for protozoology courses. This type of research is quantitative descriptive. The sources of digital data in this study were Plasmodium falciparum trophozoite and gametocyte phase preparations and Plasmodium vivax amoeboid phase. This research method includes documentation, editing, validation, description, inventory, and evaluation. The results of this study are the number of images that were successfully digitized is 158 images consisting of Plasmodium falciparum ring phase as many as 58, gametocyte phase as many as 19, and P. vivax as many as 81 images with quality including the sufficient category, the percentage of digital ATLAS usage is 73.6 while conventional ATLAS is 47.8. The conclusion of this study is that the digitalization of microscopic images of Plasmodium vivax and falciparum can be developed into an Android-based application.